Corporate governance and enterprise reform in China : building the institutions of modern markets - Tenev, Stoyan, 1961-; Brefort, Loup.; Zhang, Chunlin (Washington, D.C. : World Bank : International Finance Corporation, 2002)
This study evaluates short-and medium-term corporate governance issues impacting companies involved in ownership diversification in China. It examines problems associated with governance such as cost and framework design and makes recommendations concerning the many facets of corporate governance.
Includes bibliographical references (p. 163-168).
oif 19/03/15
Loan
Keywords: Corporate governance -- China; Corporations -- China -- Finance; Small business -- Government policy -- China; Credit -- China; Financial statements -- China; Industrial organization -- China; Capitalism -- China; Employee ownership -- China; Government ownership -- China; Industrial policy -- China; Corporations -- China; China -- Economic policy -- 2000-